Reduced sialylation of podocalyxin--the major sialoprotein of the rat kidney glomerulus--in aminonucleoside nephrosis. - Kerjaschki, D. (1985)
In this study the sugar composition of podocalyxin was determined in puromycin aminonucleoside-treated (PAN) rats and controls. Podocalyxin from both control and PAN rats bound 125I-WGA and 125I-peanut lectin (the latter only after neuraminidase treatment) on nitrocellulose transfers. Purified podocalyxin from both control and PAN rats was found to contain sialic acid, Gal, GlcNac, and Man but lacked Fuc and GalNac by gas-liquid chromatography. In PAN rats the sialic acid content of podocalyxin was reduced from 4.5% to 1.5%, whereas the concentration of the other sugars (with the possible exception of Gal) was similar to that of controls. The density of podocalyxin on the epithelial cell surface was estimated after immunogold labeling with anti-podocalyxin IgG, and no differences were found between PAN rats and controls. These data indicate that the reduced total glomerular sialic acid content found in PAN is due to the combined effects of the decreased podocyte plasmalemmal surface area and the reduced sialic acid content of podocalyxin.